2022
DOI: 10.3390/cells11071070
|View full text |Cite
|
Sign up to set email alerts
|

The Promising Therapeutic and Preventive Properties of Anthocyanidins/Anthocyanins on Prostate Cancer

Abstract: As water-soluble flavonoid derivatives, anthocyanidins and anthocyanins are the plants pigments mostly rich in berries, pomegranate, grapes, and dark color fruits. Many bioactivity properties of these advantageous phytochemicals have been reported; among them, their significant abilities in the suppression of tumor cells are of the promising therapeutic features, which have recently attracted great attention. The prostate malignancy, is considered the 2nd fatal and the most distributed cancer type in men world… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 94 publications
0
12
0
Order By: Relevance
“…Anthocyanins (ACN) are water-soluble flavonoids seen as pigments in the dark color of fruits and vegetables such as berries, pomegranates, berries, and rice [ 276 ]. They give different colors depending on their pH, they may appear red, purple, blue, or black.…”
Section: Combination Therapies Based On Selected Natural Productsmentioning
confidence: 99%
“…Anthocyanins (ACN) are water-soluble flavonoids seen as pigments in the dark color of fruits and vegetables such as berries, pomegranates, berries, and rice [ 276 ]. They give different colors depending on their pH, they may appear red, purple, blue, or black.…”
Section: Combination Therapies Based On Selected Natural Productsmentioning
confidence: 99%
“…Anthocyanins and anthocyanidins are plant pigments that account for various colors in plants and fruits. Anthocyanins are anthocyanidins structurally modified by sugar and acyl acids found mainly in dark fruits with excellent potential to inhibit tumor progression (145,146). The combination of anthocyanins, a bladder cancer preventive agent and mitomycin C has been reported to increase BLCA cell death (147).…”
Section: Flavanols Tea Polyphenols (Catechins)mentioning
confidence: 99%
“…Among a wide variety of natural compounds, anthocyanins and their derivatives were proved promising anticancer agents [ 9 ]. Mottaghipisheh et al [ 10 ] gathered many preclinical and clinical studies about the role of anthocyanins in cancer treatment. Sorrenti et al [ 11 ] confirmed that anthocyanins can induce apoptosis and suppression in prostate cancer cell proliferation.…”
Section: Introductionmentioning
confidence: 99%